Antimalarial Activity of Fagaropsis angolensis (Rutaceae) Crude Extracts and Solvent Fractions of Its Stem Bark Against Plasmodium berghei in Mice - Alemu BK; Misganaw D (Dove Medical Press, 2021)
Belete Kassa Alemu, Desye Misganaw Pharmacology and Toxicology Unit, Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, Dessie, EthiopiaCorrespondence: Belete Kassa AlemuPharmacology and Toxicology Unit, Department of Pharmacy, College of Medicine and Health Sciences, Wollo University, P O Box 1145, Dessie, EthiopiaTel +251 918330307Fax +251 333115052Email belete.kassa@wu.edu.etBackground: A current challenge in malaria control and elimination is the progressive resistance to most antimalarial drugs which necessitates the discovery of new options. Hence, the current study was initiated to investigate the antimalarial activity of the stem bark of Fagaropsis angolensis in mice.Methods: The test material was extracted using 80% methanol in a cold maceration technique and further fractionated in solvents of varied polarity. Acute oral toxicity was assessed following the OECD guideline no. 425 protocol. Then, the antimalarial activities of the crude extract and the fractions were evaluated in a 4-day suppression test. Rane’s test was also used to evaluate the curative potential of the n-butanol fraction that showed the highest effect during the 4-day suppressive test. Parameters such as parasitemia suppression, mean survival time, packed cell volume, rectal temperature, and body weight were determined to establish the activity.Results: The acute oral toxicity test indicated that the plant did not cause any signs of behavioral changes or mortality at 200 mg/kg limit dose. In a 4-day suppression test, a significant dose-dependent reduction in the parasitemia level and prolongation of survival time were observed (p< 0.001) in all three doses of the crude extract compared with the negative control. The crude extract also exhibited a significant (p< 0.001) protective effect in packed cell volume and rectal temperature decline in all three doses in a dose-dependent fashion compared with the negative control. Among all fractions, the n-butanol fraction displayed the highest effects in all parameters in the 4-day suppression test. In addition, the n-butanol fraction also showed a significant percentage of parasitemia suppression effects at all doses in Rane’s test. Furthermore, higher free radical scavenging activity was observed in the n-butanol fraction and the 80% methanol extract.Conclusion: This study established that Fagaropsis angolensis had shown potential antimalarial activity as evidenced by the significant effects in the different parameters, upholding its traditional use for the treatment of malaria and laying the foundation for further investigations.Keywords: antimalarial activity, Plasmodium berghei, Fagaropsis angolensis, parasitemia, antioxidant activity